Synthesis and Circular Dichroism of 5- and 6-Halogenobicyclo[2.2.1]hept-5-en-2-ones; Tests for the Dekkers' Quantitative Chirality Rule - Antonella Lettieri; Pierre-Alain Carrupt; Pierre Vogel (CHIMIA)
Stereoselective syntheses of (+)-(1R,4R)-5-chloro-, -5-bromo-, -6-chloro-, and -6-bromobicyclo[2.2.1]hept-5-en-2-ones ((+)-2-(+)-5) are presented. The chiroptical properties (CD spectra) of these halogenated derivatives are compared with those of the non-substituted (+)-(1R,4R)-bicyclo[2.2.1]hept-5-en-2-one ((+)-1) and analyzed in the light of the General Octant Rule and the Dekkers’ Quantitative Chirality Rule for the highest wavelength Cotton Effects of β,γ-enones.